Quantitative evaluation and optimization of carbon sequestration in Chongqing’s parks under the ‘dual carbon’ strategy - Liu, Peng; Quan, Feng; Gao, Yuxuan (Oxford University Press, 2025)
To quickly and efficiently evaluate the carbon sequestration benefits of urban parks, a quantitative evaluation method for carbon sequestration is designed taking sponge city parks as an example. The correlation between the average diameter at breast height of plants and the net primary productivity of vegetation was the strongest. Through optimized design, urban parks can better integrate the positive and negative benefits of sponge facilities, effectively enhancing their carbon sink capacity. At the same time, by promoting and applying the construction concepts and technical means of sponge-type parks, the study is expected to form more green spaces within the city.